Manet Simulation Through Opnet - et. al., Dr. Ravikant Zirmite, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper presents the results of a detailed packet-level simulation comparing three multi-hop wireless ad hoc network routing protocols under the load of different probability distributions, that cover a range of design choices having different protocol viz. AODV,OLSR and TORA. We have extended the OPNET network simulator to accurately model the MAC and physical-layer behavior of the IEEE 802.11 wireless LAN standard, including a realistic wireless transmission channel model. Simulation of 100 mobile nodes has been carried out and the performance optimization is determined.